Autonomic Dysfunction Because of Severe Tetanus in an Unvaccinated Child - Ting-Syuan Lin; Li-Kuang Chen; Teng-Yi Lin; Shu-Hui Wen; Ming-Chun Chen; Rong-Hwa Jan (Elsevier, 2011)
Tetanus is rare in a country with a national vaccination program. When it does occur, the associated autonomic dysfunction is a challenge for physicians. We report here a case of an unvaccinated 5-year-old boy who suffered from tetanus complicated by autonomic dysfunction, which was successfully controlled by the infusion of magnesium sulfate. This is the first case that demonstrated the therapeutic effect of magnesium sulfate in a child with tetanus. This case highlights the importance of implementing a vaccination program.